Occupational injuries among children and adolescents in Cusco Province: A cross-sectional study (2014)
Although the number of child laborers in Latin America is generally high, data on occupational hazards and injuries is insufficient. The objective of this study was therefore to determine the lifetime prevalence of and risk factors for occupational injuries among working students (10-17 years old) in Cusco Province. Methods. A cross-sectional study was conducted at five public night schools. 375 students (response 91.5%) completed an interview-based questionnaire on socio-demographics, work-related factors, and lifetime prevalence of occupational injuries. Multiple logistic regression analyses were performed to estimate risk factors for different types and causes of occupational injuries. Results: Falls (11%), car accidents (9%) and physical violence (3%) were common causes of injuries in this population. Severe injuries (fractures, luxation or amputations) were reported by 3% of the population. A high daily income (?20 PEN, ?15 USD) was a statistically significant predictor for injuries caused by falls [OR 2.8; 95% CI 1.2-6.5] and physical violence at work [12.1; 1.3-115.9] whereas children born in Cusco and those working in the service sector were at higher risk of injuries caused by car accidents [3.7; 1.5-9.3 and 4.2; 1.2-15.3]. Conclusions: Occupational accidents among child workers attending public night schools are common in Cusco with a lifetime prevalence of 3% for severe injuries. High income seems to convince child laborers to accept poor working conditions. © 2014 Schlick et al.; licensee BioMed Central Ltd.